Detection of trihalomethane (chloroform) in drinking water in Baghdad city: Zuhair A. Mohammed , Shalal M. Hussein , Odae Satar abbas - Mohammed, Zuhair A. (The Iraqi Journal of Veterinary Medicine, 2009)
This study designed to determine the chloroform concentration in drinking water in Baghdad city. Thechloroform concentration specified into drinking wter into four portions per a week along two weeks in eachmonth for three months of this study (August, October and December) , 2008 each portion has two samples,so the total number be 48 drinking water samples (sixteen samples per month as an equal portions for eachproject and district).Four projects of water supply filtration stations were selected in Baghdad city, two of them were in Kerkhside (include Qadissia water supply project and Al-karama water supply project). The other two projects inthe Rusafa side, include Al-wahda and Al-Wathba water supply projects. In addition to the citizen districthouses as Al-Qadissia, Al-Otayfia, Al-Karrada and Bab Al-Muathem respectively.The chloroform concentration was determined by the use of the Gas Chromatographic (GC) in thelaboratories of the general technology state for water treatment which belongs to the Ministries of Scienceand Technology.The results revealed the concentration of drinking water in Baghdad city by chloroform, comparison ofthese results between each others revealed that the citizen district houses gave high average of chloroformconcentration than the projects along the period of this study.According to the statistical data analysis it was found that the results in August were the highest andsignificantly transcend (p < 0.05) than the results reported in October and December in all the drinkingwater project and citizen district.On other hand it was noticed that the Wathba project and Bab Al-Muathemdistrict houses significantly transcend (p < 0.05) than other water drinking projects and citizen districtsin theaverage mean along all month of study.In addition, the statistical data analysis found out a strong forward relation ship between the decreasechloroform concentration and decrease of temperature degrees whenever going to the cold season of theyear, in all the water drinking project and citizen district.